Political Corruption and CEO Compensation Design - Yang, Jingyu; Yu, Yangxin; Zheng, Liu (The Accounting Review, 2026)
ABSTRACT This study examines the impact of political corruption on the provision of CEO risk-taking incentives. We hypothesize that firms adjust their CEO’s risk-taking incentives to reflect the influence of local political corruption on the firms’ desired level of risk-taking. Using U.S. Department of Justice data on local political corruption, we find that the sensitivity of CEO wealth to stock volatility (vega) is lower in firms located in high-corruption districts. The negative impact of corruption on vega is more pronounced among (1) firms operating in industries that are more dependent on government procurement, (2) firms operating in more innovative industries, and (3) firms without political connections. Our study offers new insights into how the institutional environment shapes executive compensation design. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G32; G38; J33; J41; M52.